What Is the Impact of AI on Clinical Workflow Efficiency? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
In the ever-evolving landscape of healthcare, the quest for greater efficiency is a constant pursuit. Clinicians are often bogged down by a mountain of admin...
Keywords: AI in Clinical Decision Support; Impact; Clinical; Workflow; Artificial Intelligence; Healthcare; Patient Care